One-off Export Events - Ingo Geishecker; Philipp J.H. Schröder; Allan Sørensen (Center for Economic Studies and ifo Institute (CESifo), 2016)
An astonishing 33% of all firm-product-destination export spells in Danish data turn out to be isolated single-month one-off export events (observed once in a 49 month window). On average, for an export-active firm, such one-off exports account for 17% of total foreign sales. These patterns cannot be explained by the lumpiness of trade (e.g., seasonal shipments), nor do they sit well with available models of trade. To reconcile the data with theory, we propose a model that includes passive (i.e., buyer-side driven) one-off exporting in addition to the customary proactive export channel. This framework guides our empirical investigation. We find that one-off exports arise relatively more often to far-away, low-income or unstable destinations; moreover, one-off exporting is associated with lower productivity and smaller firm size.
Keywords: F12; F14; L10; D40; 330; passive exporting; proactive exporting; export duration; temporary trade; monthly transactions data; firm-level data; heterogeneous firms